Structure and Expression of Class II Defective Herpes Simplex Virus Genomes Encoding Infected Cell Polypeptide Number 8 - Locker, Hilla (1982)
Defective genomes present in serially passaged virus stocks derived from the tsLB2 mutant of herpes simplex virus type 1 were found to consist of repeat units in which sequences from the U(L) region, within map coordinates 0.356 and 0.429 of standard herpes simplex virus DNA, were covalently linked to sequences from the end of the S component. The major defective genome species consisted of repeat units which were 4.9 × 10(6) in molecular weight and contained a specific deletion within the U(L) segment. These tsLB2 defective genomes were stable through more than 35 sequential virus passages. The ratios of defective virus genomes to helper virus genomes present in different passages fluctuated in synchrony with the capacity of the passages to interfere with standard virus replication. Cells infected with passages enriched for defective genomes overproduced the infected cell polypeptide number 8, which had previously been mapped within the U(L) sequences present in the tsLB2 defective genomes. In contrast, the synthesis of most other infected cell polypeptides was delayed and reduced. The abundant synthesis of infected cell polypeptide number 8 followed the β regulatory pattern, as evident from kinetic studies and from experiments in which cycloheximide, canavanine, and phosphonoacetate were used. However, in contrast to many β (early) and γ (late) viral polypeptides, the synthesis of infected cell polypeptide number 8 was only minimally reduced when cells infected with serially passaged tsLB2 were incubated at 39°C. The tsLB2 mutation had previously been mapped within the domains of the gene encoding infected cell polypeptide number 4, the function of which was shown to be required for β and γ viral gene expression. It is thus possible that the tsLB2 mutation affects the synthesis of only a subset of the β and γ viral polypeptides. An additional polypeptide, 74.5 × 10(3) in molecular weight, was abundantly produced in cells infected with a number of tsLB2 passages. This polypeptide was most likely expressed from truncated gene templates within the most abundant, deleted repeats of tsLB2 defective virus DNA.